Imaging work-up and endovascular treatment options for aorto-enteric fistula - Partovi, Sasan; Trischman, Thomas; Sheth, Rahul A.; Huynh, Tam T. T.; Davidson, Jon C.; Prabhakar, Anand M.; Ganguli, Suvranu (Cardiovascular Diagnosis and Therapy; Vol 8, Supplement 1 (April 13, 2018): Cardiovascular Diagnosis and Therapy (Advanced aortic imaging and intervention), 2017)
Aorto-enteric fistula (AEF) is a rare life-threatening condition. Early recognition and diagnosis are of paramount importance to improve outcome. In this article four cases of AEF with relevant pre- and post-procedural images are presented to demonstrate the utility of cross-sectional imaging in the work-up of AEF. The literature is reviewed to describe the typical presentation of AEF, the diagnostic work-up of AEF, and the different methods used to treat AEF. Endovascular repair of AEF is gaining increasing attention due to its decreased short-term mortality compared to open surgical techniques.